2016
DOI: 10.5586/aa.1676
|View full text |Cite
|
Sign up to set email alerts
|

Development and production response of edible and forage varieties of pea (Pisum sativum L.) to temporary soil drought under different levels of phosphorus application

Abstract: The change in weather conditions in Central Europe has led to the need to review current standards for fertilization of pulse crops. Physiologists claim that phosphorus may play a significant role in raising tolerance to a temporary lack of water in the soil. The objective of the 2-year field study (2011)(2012) was to assess the effect of phosphorus application on characteristics of the aerial and underground plant parts of different varieties of pea and elements of their yield structure. The study showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…On the basis of their analysis of regression trees, Zheng et al (2010) proved that in the condition of soil drought, the productivity of soybean plants is conditioned on the quantity of phosphorus applied. Similar results were obtained by Klimek-Kopyra et al (2016) who indicated that phosphorus had significant importance in the increase of productivity of plants under temporary soil drought. The above results were confirmed in our experiment because the significant impacts of phosphorus and weather conditions were forecasted through NDVI.…”
Section: Discussionsupporting
confidence: 88%
“…On the basis of their analysis of regression trees, Zheng et al (2010) proved that in the condition of soil drought, the productivity of soybean plants is conditioned on the quantity of phosphorus applied. Similar results were obtained by Klimek-Kopyra et al (2016) who indicated that phosphorus had significant importance in the increase of productivity of plants under temporary soil drought. The above results were confirmed in our experiment because the significant impacts of phosphorus and weather conditions were forecasted through NDVI.…”
Section: Discussionsupporting
confidence: 88%
“…It is a vital element and is classified as a macronutrient on account of the relatively large amounts required by the plants (Rajkhowa, 1992). It functions as one of the key elements in the process of photosynthesis, nutrient transport, and energy transfer (Klimek-Kopyra et al, 2016). Phosphorus is a vital macronutrient that is required to meet global food supplies and make crop and livestock production lucrative (Raj & Tripathi, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Among these nutrients, phosphorus is particularly a critical component because it is limiting, on a large proportion of global arable land, for crop yield, and it is a nonrenewable resource (Aliabadi Farahani et al, 2008). Phosphorus is crucial for plant growth and constitutes approximately 0.2% of plant dry weight; however, it is one of the nutrients most difficult for plants to acquire (Klimek-Kopyra et al, 2016). It is the second most important nutrient after nitrogen; it affects plant growth and yield and plays important roles in physiological processes such as cell division and development, energy transfer (ATP and ADP), signal transduction, macromolecular biosynthesis, photosynthesis, and plant respiration (Das et al, 2015).…”
Section: Introductionmentioning
confidence: 99%